Towards Identifying, Understanding and Controlling Cumulative Revelations in Social Media. Issue 1 (13th October 2021) - Nicol, Emma; Htait, Amal; Azzopardi, Leif; Moncur, Wendy
Abstract: Every day, people post information about themselves and others on online social networks, making such information accessible within their social circles but also, potentially, way beyond. While the information posted may seem benign or innocuous, small pieces of information, when tied together, can potentially reveal much more about the person than intended. Such cumulative revelations could expose them to risks such as identity theft, fraud or loss of employment. This paper describes findings from interviews about people's online interactions, focusing on their requirements and desires for improved ways to identify, understand and control cumulative revelations arising from their social media profiles that could put them at risk of grave consequences. These findings motivate our future work on how to better raise awareness among social media users of the risks and consequences to which combinations of posts may lead.